Rastreamento de artrite psoriásica – utilização do instrumento pest-bp em pacientes com psoríase do ambulatório de dermatologia do Hospital Universitário de Santa Maria - Thomé, Vanessa (2023)
Psoriatic arthritis is a condition that affects approximately one-third of individuals with psoriasis, often manifesting around ten years after the onset of the initial skin lesions. Due to the variability in the course of the disease, with the potential for joint deformities and an impact on quality of life, it is crucial for dermatologists to identify early signs and symptoms of joint involvement. The objective of the study was to assess the accuracy of the "Psoriasis Epidemiology Screening Tool – PEST-BP" questionnaire for screening psoriatic arthritis and to estimate the prevalence of this disease among psoriasis patients attending the Dermatology outpatient clinic at the University Hospital of Santa Maria. One hundred patients who agreed to respond to the questionnaire during their dermatological consultation were evaluated. Subsequently, these patients were referred for assessment by a rheumatologist, who diagnosed psoriatic arthritis based on CASPAR criteria. The PEST-BP questionnaire demonstrated an accuracy of 80%, with a sensitivity of 81% and specificity of 79.9% for scores ≥ 3. The prevalence of psoriatic arthritis in this population was 21%, with obesity being the most common comorbidity, present in 39% of the patients. Among the factors associated with the diagnosis of psoriatic arthritis, there was a stronger association in patients with severe psoriasis (PASI ≥ 10) and PEST ≥ 3. The data from the study indicate that the PEST-BP tool is effective in screening for psoriatic arthritis, potentially assisting dermatologists in identifying patients at a higher risk of joint involvement.